Exploration of electrochemical energy storage potential of MWCNT scaffolds functionalized with Lu2FeMnO6 synthesized via a facile sol–gel Pechini chemical method - Vahid Rahimkhoei; Masoud Salavati-Niasari; Forat H. Alsultany; Aseel M. Aljeboree; Masood Hamadanian (Applied Water Science)
Abstract Lately, there has been considerable attention directed toward the development of a hydrogen storage cell power system that is both environmentally friendly and free from pollution. In the past decade, numerous notable advancements in methods of energy storage have emerged, influencing research, innovation, and the potential direction for enhancing our comprehension of energy storage. In the present research, the sol–gel Pechini methodology was utilized to synthesize Lu2FeMnO6 nanostructures and evaluate their viability as hydrogen storage materials for the inaugural time. The influence of stabilizing agents, the molar ratio of the gelling agent to the stabilizing agent, and the calcination temperature were meticulously examined to attain the optimal dimensions and morphological characteristics. While researchers have a growing interest in hydrogen energy, the application of double perovskite nanostructures for hydrogen absorption has not yet been explored. Diverse dimensions and configurations of nanocomposites were scrutinized utilizing scanning electron microscopy (SEM) and transmission electron microscopy (TEM). X-ray diffraction (XRD), energy-dispersive X-ray (EDX), and Fourier transform infrared (FT-IR) analyses were conducted to ascertain the purity and chemical compositions of the nanocomposites. Among the various methodologies employed for hydrogen storage, the electrochemical approach is recognized as one of the most efficacious, as it facilitates the generation and storage of hydrogen under standard temperature and pressure conditions. This investigation explored the ramifications of integrating varying concentrations of multi-walled carbon nanotubes (MWCNT) to augment the hydrogen storage capacity of a composite material through an electrochemical methodology. The Lu2FeMnO6/MWCNT nanocomposites exhibited optimal performance when the concentration of MWCNT was set at 2%, achieving a discharge capacity of 540.27 mAhg−1 after 15 cycles in a 2 M KOH electrolyte, which represents a 2.45-fold enhancement compared to the capacity demonstrated by Lu2FeMnO6 nanostructures. This investigation elucidates a promising methodology for the advancement of more efficient electrode materials via the integration of double perovskites.